Sleep problems in prostate cancer patients: a comparison of several questionnaires measuring sleep quality - Hinz, Andreas; Schulte, Thomas; Friedrich, Michael; Ernst, Jochen; Petrowski, Katja; Mehnert-Theuerkauf, Anja (Frontiers in Psychology, 2026)
ObjectiveProstate cancer (PCa) patients often suffer from sleep problems. The aims of this study were to compare several questionnaires for measuring sleep problems, to compare the sleep problems of PCa patients with those of the general population, to calculate associations between sleep problems and other variables, and to analyze the factor structure of sleep items.MethodsA sample of 309 PCa patients treated in a German rehabilitation hospital were examined. Their sleep problems were assessed with the Pittsburgh Sleep Quality Index (PSQI), the Insomnia Sleep Scale (ISI), the Jenkins Sleep Scale (JSS), and two single-item measures. In addition, questionnaires on quality of life, anxiety, depression, and fear of cancer recurrence were used.ResultsSleep quality in the PCa group was markedly worse than that of the general population, with effect sizes between 0.69 and 0.97. The correlations between the sleep scales ranged from 0.64 to 0.84, which indicates a certain but not complete interchangeability. Sleep problems were associated with anxiety, depression, and fear of cancer recurrence. A principal component analysis yielded three factors underlying the items of the sleep instruments.ConclusionThe study confirmed sleep problems in PCa patients. Results obtained by using one specific questionnaire can only be partly generalized to other instruments.